Understanding the Intersectional Challenges of LGBTQ community in the Indian Society: A Systematic Review Paper - Saanvi Gupta; Deepika Chamoli Shahi (Recent Trends in Social Studies, 2025)
This study examines the intersectional issues that the LGBTQ population faces in Indian society, examining how their lived experiences are shaped by caste, class, religion, and regional differences. The purpose of this study is to investigate how the experiences of LGBTQ people in India are impacted by several axes of identification, including caste-based discrimination, economic position, geographical inequities, and religious biases. 43 research papers have been reviewed from which 30 papers have been included and 13 have been excluded. Research papers from following databases are reviewed - Pub med, Springer, research gate, science direct, Wiley online library, sage pub, academia etc. Systematic review of 30 research papers has been done in the article. This review examines the particular difficulties LGBTQ+ people from various socioeconomic and geographic origins encounter, emphasizing problems including lack of legal recognition of same-sex weddings, family rejection, job discrimination, and healthcare access. It also looks at how the media, policy changes, and grassroots movements shape narratives and promote social change. In order to guarantee equality and dignity for every member of the LGBTQ+ population in India, the report emphasizes the necessity of inclusive policies and social acceptance.
Keywords: Indian society; Intersectional challenges; LGBTQ; community